Slow scholarship for social work: A praxis of resistance and creativity. (January 2022) - Wahab, Stéphanie; Mehrotra, Gita R; Myers, Kelly E
Expediency, efficiency, and rapid production within compressed time frames represent markers for research and scholarship within the neoliberal academe. Scholars who wish to resist these practices of knowledge production have articulated the need for Slow scholarship—a slower pace to make room for thinking, creativity, and useful knowledge. While these calls are important for drawing attention to the costs and problems of the neoliberal academy, many scholars have moved beyond "slow" as being uniquely referencing pace and duration, by calling for the different conceptualizations of time, space, and knowing. Guided by post-structural feminisms, we engaged in a research project that moved at the pace of trust in the integrity of our ideas and relationships. Our case study aimed to better understand the ways macro forces such as neoliberalism, criminalization and professionalization shape domestic violence work. This article discusses our praxis of Slow scholarship by showcasing four specific key markers of Slow scholarship in our research; time reimagined, a relational ontology, moving inside and towards complexity, and embodiment. We discuss how Slow scholarship complicates how we understand constructs of productivity and knowledge production, as well as map the ways Slow scholarship offers a praxis of resistance for generating power from the epistemic margins within social work and the neoliberal academy.